The Impact of Profit-and-Loss Sharing (PLS) and Non-PLS Sharia Financing on Economic Growth: A VECM Approach - Marina Oktari; R Moh Qudsi Fauzi; Sulistya Rusgianto (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study examines the impact of profit-sharing (mudharabah and musyarakah) and non-PLS (murabahah and qardh) Islamic financing schemes on Indonesia's economic growth by disentangling the short-run dynamics from the long-run equilibrium adjustment through a Vector Error Correction Model (VECM). Quarterly data of real GDP per capita and total Islamic financing by contract type for 2015 Q1-2023 Q4 are analyzed. Stationarity was assessed by the Augmented Dickey-Fuller test, cointegration through the Johansen procedure, and optimal lag selection by the likelihood ratio criterion. The VECM framework estimates error correction coefficients and short-run dynamic coefficients, complemented by Granger causality, impulse response function (IRF), and variance decomposition (VD) tests to explore feedback between variables and shock propagation. The short-term dynamics show no significant effect of Islamic financing instruments on growth. In the long run, musyarakah has a significant negative impact, while qardh has a significant positive impact. Variance decomposition shows that PLS instruments collectively explain 6.4-7.9 percent of the variance in GDP growth over ten quarters. This study contributes to developing financing strategies to achieve stable and sustainable financing.